PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK SEBAGAI UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN BANGUN RUANG PADA SISWA KELAS IVA SDN 9 SESETAN TAHUN PELAJARAN 2011/2012 - I Gusti Ayu Arista Widari; I Gusti Ngurah Nila Putra; I Ketut Suwija (Jurnal Santiaji Pendidikan (JSP), 2013)
The aim of this action research is to know whether there is an improvement in learning activity and achievement of grade IV students in learning three dimension shapesthrough the implementation of realistic approach. This research was conducted in Primary school 9 Sesetan in the academic year 2011/2012. The subjects of this study were 45 students of grade IV Primary school 9 Sesetan. The data collected in this research covered: students’ learning activity which was collected from observation, and students’ achievement data which was collected through some achievements test in form of objective and essay. This research was conducted in two cycles. The result of this study shows that the students’ learning activity in cycle one was quite active, and in cycle two the students’ learning activity was categorized as active. From the achievement of the students it was found that the average score, learning capacity, and learning outcome from the pre-cycle, cycle 1, and cycle 2 consecutively are: 4.98, 49.80% and 26.67%; 6.66, 66.60% and 53.30%; then 8.20, 82% and 91.10%. From the result of data analysis and discussion, then it can be concluded that there is an improvement in terms of students’ learning activity and achievement of IV grade students of Primary school 9 Sesetan in the academic year 2011/2012 in learning three dimension shapes through the use of realistic approach.